Synthesis, spectral characterization and in vitro antibacterial evaluation and Petra/Osiris/Molinspiration analyses of new Palladium(II) iodide complexes with thioamides. Issue 3 (1st September 2016) - Nadeem, Shafqat; Sirajuddin, Muhammad; Ahmad, Saeed; Tirmizi, Syed Ahmed; Ali, Muhammad Irshad; Hameed, Abdul
Abstract: The paper emphasizes on the synthesis of Palladium(II) iodide complexes containing based ligands. The new compounds of general formulae [Pd(L)4 ]I2 where L = Thiourea (Tu), Methylthiourea (Metu), Dimethylthiourea (Dmtu), Tetramethylthiourea (Tmtu), Imidazolidine-2-thione (Imt), Mercaptopyridine (Mpy), Mercaptopyrimidine (Mpm), and Thionicotinamide (Tna) were prepared simply by reacting K2 [PdCl4 ] with the corresponding thioamides in 1:2 M ratio and then with 2 equivalents Potassium iodide. The complexes were characterized by elemental analysis and spectroscopic techniques (IR, 1 H and 13 C NMR). All the synthesized complexes were screened for antibacterial activity and some of compounds have shown good activities against both gram positive and gram negative bacteria. POM analyses reveal that the compounds are only slightly toxic and present a potential for antibacterial activity. Moreover, they have 16–23% drug score which is an important parameter for the compound possessing the drug properties.